Analysis of risk factors and prognosis of cytomegalovirus infection post umbilical cord blood stem cell transplantation in children with primary immunodeficiency diseases - Wei, Z L (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2022)
Objective: To investigate the risk factors and outcomes of cytomegalovirus (CMV) infection post umbilical cord blood stem cell transplantation (UCBT) in children with primary immunodeficiency diseases (PID). Methods: Clinical data of 143 PID children who received UCBT in the Children's Hospital of Fudan University from January 2015 to June 2020 were collected retrospectively. CMV-DNA in the plasma was surveilled once or twice a week within 100 days post-UCBT. According to the CMV-DNA test results, children were divided into the CMV-infected group and the CMV-uninfected group. The incidence and risk factors of CMV infection were analyzed. At 1-month post-UCBT, the absolute lymphocyte count, ratio of lymphocyte subsets and immunoglobulin levels were compared between those whose CMV infection developed 1-month later post-UCBT and those not. Mann-Whitney U test and chi-squared test were used for comparision between groups. Kaplan-Meier survival analysis was used to analyze the impact of CMV infection on survival. Results: Among 143 patients, there were 113 males and 30 females, with a age of 14 (8, 27) months at UCBT. Chronic granulomatosis disease (n=49), very-early-onset inflammatory bowel disease (n=43) and severe combined immunodefiency (n=29) were the three main kinds of PID. The rate of CMV infection was 21.7% (31/143), and the time of infection occurring was 44 (31, 49) days post-UCBT. The incidence of recurrent CMV infection was 4.2% (6/143) and refractory CMV infection was 4.9% (7/143).There was no significant difference in the first time CMV-DNA copy and peak CMV-DNA copy during treatment between the recurrent CMV infection group and the non-recurrent CMV infection group (32.8 (18.3, 63.1)×106 vs. 22.5 (13.2, 31.9)×106 copies/L, Z=-0.95, P=0.340;35.2 (20.2, 54.6)×106 vs. 28.4 (24.1, 53.5)×106copies/L, Z=-0.10, P=0.920), so were those between the refractory CMV infection group and non-refractory CMV infection group (21.8 (13.1, 32.2)×106 vs. 25.9 (14.2, 12.2)×106copies/L, Z=-1.04, P=0.299; 47.7 (27.9, 77.6)×106 vs. 27.7 (19.7,51.8)×106copies/L, Z=-1.49, P=0.137). The CMV-infected group accepted more reduced-intensity conditioning (RIC) regimen than the CMV-uninfected group (45.2% (14/31) vs. 25.0% (28/112), χ2=4.76, P<0.05). The rate of CMV-seropositive recipients and Ⅱ-Ⅳ acute graft versus host diseases (aGVHD) are significantly higher in the CMV-infected group than the CMV-uninfected group (100% (31/31) vs. 78.6% (88/112), 64.5% (20/31) vs. 26.8% (30/112), χ2=7.98,15.20, both P<0.05). The follow-up time was 31.6 (13.2, 45.9) months, CMV infection had no effect on overall survival (OS) rate (χ2=0.02, P=0.843). There was significant difference in the survival rate among three groups of refractory CMV infection, non-refractory CMV infection and the CMV-uninfected (4/7 vs.95.8% (23/24) vs. 86.6% (97/112), χ2=5.91, P=0.037), while there was no significant difference in the survival rate among three groups of recurrent CMV infection, non-recurrent CMV infection and the CMV-uninfected (5/6 vs. 88.0% (22/25) vs. 86.6% (97/112), χ2=0.43, P=0.896). Children who developed CMV infection after 30 days post-UCBT had lower absolute count and rate of CD4+ T cells and immunoglobulin G (IgG) level than those in the CMV-uninfected group (124.1 (81.5, 167.6) ×106 vs. 175.5 (108.3, 257.2) ×106/L, 0.240 (0.164, 0.404) vs. 0.376 (0.222, 0.469), 9.3 (6.2, 14.7) vs. 13.6 (10.7, 16.4) g/L, Z=-2.48, -2.12,-2.47, all P<0.05), but have higher rate of CD8+T cells than those in CMV-uninfected group (0.418 (0.281, 0.624) vs. 0.249 (0.154, 0.434), Z=-2.56, P=0.010). Conclusions: RIC regimen, grade Ⅱ-Ⅳ aGVHD and CMV-seropositive recipients are the main risk factors associated with CMV infection in PID patients post-UCBT. Survival rate of children with refractory CMV infection after UCBT is reduced. Immune reconstitution in children after UCBT should be regularly monitored, and frequency of CMV-DNA monitoring should be increased for children with delayed immune reconstitution